Grafting enhances drought stress tolerance by regulating the proteome and targeted gene regulatory networks in tomato - Pritam Paramguru Mahapatra; Pritam Paramguru Mahapatra; Dong Won Bae; Michitaka Notaguchi; Sowbiya Muneer (Frontiers in Plant Science)
Tomato (Solanum lycopersicum), a widely cultivated yet perishable crop, depends heavily on adequate sunlight and water for optimal growth and productivity. However, due to unavoidable environmental and climatic changes—particularly drought—its productivity has declined in recent years. Grafting, an ancient horticultural practice, is known to enhance yield and combat abiotic stress by regulating physiological and cellular processes. The present study investigated drought tolerance in tomato at both the proteomic and transcriptomic levels. During the initial physiological screening stage, two drought-resistant genotypes of Solanum lycopersicum were selected as rootstocks and drought-susceptible genotypes as scions. Among six genotypes evaluated under drought stress (based on relative water content, chlorophyll fluorescence, and stomatal conductance), graft combinations G1 and G4 demonstrated superior performance. These combinations were subsequently selected for molecular analyses to investigate gene expression patterns and stress-responsive pathways. Our findings revealed that grafting susceptible tomato genotypes onto resistant rootstocks mitigated the deleterious effects of drought stress by improving photosynthetic pigment levels and reducing oxidative stress. A proteomic investigation observed that grafting improved cellular responses, metabolic processes, and stress response pathways. Furthermore, transcriptomic studies of stress-related genes, including DREB, WRKY, PIPs, SOD, CAT, APX, HSPs, and LOX, revealed enhanced stress tolerance in the G1 and G4 graft combinations.